GENETIC PREDICTORS FOR CARDIOEMBOLIC STROKE IN PATIENTS WITH ATRIAL FIBRILLATION - V. A. Shulman; N. V. Aksiutina; S. Yu. Nikulina; B. V. Nazarov; K. V. Dudkina; V. N. Maksimov; V. V. Kozlov; M. Yu. Kotlovsky; S. F. Sinyapko; I. M. Platunova (Российский кардиологический журнал)
Aim. To reveal genetic predictors of the ischemic stroke in patients with AF. Material and methods. Totally 121 patient studied with AF and 155 their relatives of I-III grade of relation. First group consisted of 43 probands with AF and stroke anamesis and 54 their relatives, the second group – 78 probands with AF without stroke and 101 their relative. Control group consists of 188 subjects. The patients underwent ECG, EchoCG, Holter ECG-monitoring, VEM, TELAS, molecular-genetic investigation.Results. Genotype AA of polymorphism -455 G>A of gene FGB statistically significantly predominated in subjects with AF and stroke comparing to those with AF without stroke (20,94% vs 6,4%; p=0,036). Risk relation shows that the chance of stroke development with AA homozygous genotype at rare allele is 3,9 times higher than in its absence. Overall the genotypes CT and TT by the rare allele 807C>T gene ITGA2 statistically significantly predominated in the patients with AF and stroke comparing to controls (76,7% vs 56,9%, p=0,026). The chance of stroke development while carrying CT and TT by the rare allele is 2,5 times higher than in their absence. Genotypes TC and CC by the rare polymorphism 5 T>C gene GPIBA statistically more significantly were found in patients with AF and credibly increasesthe chance for stroke 2,3 times. Allele A of polymorphism 10796 G>A gene F7 statistically more significant rarer found in patients with AF and stroke comparing to controls (6,98% vs 16,22%; p=0,043). Chance of stroke in absence of allele A is 2,6 times higher, than in its presence.Conclusion. The study revealed that homozygous genotype AA by the rare polymorphism -455G>A gene FBG, heterozygous CT and homozygous TT by the rare allele 807C>T gene ITGA2, heterozygous TC anf homozygous CC by the rare – 5 T>C gene GPIAB are set as genetic predictors for ischemic stroke development in AF. Allele A of the polymorphism 10976 G>A gene F7 show protective effect in the ischemic stroke development in AF. Genetic risk estimation might improve the primary ischemic stroke prevention in AF.